Principal component and cluster analyses based on morphological characterization in sugarcane - Alarmelu, Srinivasan; Govinda Kurup, Hemaprabha (Journal of Sugarcane Research, 2023)
Morphological descriptors are important to breeders, researchers and sugarcane growers for practical and scientiﬁc purposes and for the protection of new varieties and maintenance of genetic purity and uniformity in a variety. The popular and released sugarcane varieties for peninsular zone from ICAR-SBI were characterized using descriptors. Morphological observations of 21 sugarcane cultivars viz., Co 86032, Co 99004, Co 94008, Co 0209, Co 0212, Co 0304, Co 0310, Co 0312, Co 0314,Co 2001-13, Co 2001-15, Co 06029, Co 10024, Co 10025, Co 10026, Co 10027, Co 12009, Co 14026, Co 15005, Co 16006 and Co 16008 was carried out on 20 growth characters viz., plant habit, leaf canopy, trashing nature, auricle, dewlap, ligule, internode and node etc., Among them, 7 were dimorphic and 13 were found to be polymorphic. The dendrogram based on UPGMA using morphological characters, grouped twenty one sugarcane cultivars into ﬁve groups. The principal component analysis of 20 characters showed that the total variation contributed to PCA simpliﬁes twenty qualitative traits into twenty PC axes with eigen value > 1 and with cumulative variance of 65.30 %, remaining components with eigen value < 1 contributed to 35.72 % of the variability. The information about morphological variations in this study suggests that morphological characters are very important for identifying sugarcane cultivar variations and for understanding closeness of their parents. The varieties under study recorded a wide range of variation for most of the morphological traits can be utilized for further crop improvement programmes and also as a practical guide for breeders.